The Pengembangan Desain Media Pembelajaran Bahasa Arab dan Materinya berbasis New Media berdasarkan Kurikulum 2013 di Madrasah Aliyah Negeri Sidoarjo - Nuriya Maslahah (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
State education world nowadays facing the advance technology of industry revolution, which mean all teaching and learning activity should follow and implement technology also. Education evaluation including study subject in almost all school has started to implement digital evaluation, including MAN Sidoarjo. Otherwise, it is only limited to evaluation; hasn’t guided to teaching media and its materials. Therefore, researcher will try to offer a teaching media design and materials based on state curriculum 2013. The purpose of this research is to know the Arabic teaching media design and its materials based on new media in MAN Sidoarjo. The research method used is descriptive qualitative of research and development design from Borg & Gall level 4 up to designing the product. The result of this research is expected to produce a teaching media based on new media in the form of website especially for teaching Arabic language including practices and the test which is expected can solve the problems of teaching Arabic language in MAN Sidoarjo. Key Words: Teaching media, Teaching materials, New Media, Curriculum 2013.